Burundi : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents key findings of the First Review for Burundi under the Poverty Reduction and Growth Facility (PRGF). Economic growth in Burundi increased to 4.5 percent in 2008, mainly because of a good coffee harvest and more donor-financed projects. The economic outlook is generally positive but subject to risks arising from the security situation and the external environment. Performance under the PRGF-supported program has been broadly satisfactory. All quantitative and structural performance criteria at end-September 2008 were met, and structural reforms are proceeding.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet